IMPROVEMENT OF BUSINESS MANAGEMENT AND BUSINESS FINANCIAL MANAGEMENT ON BANANA CHIPS MSMES IN KAMURANG VILLAGE, CIKANDE DISTRICT, SERANG REGENCY - Encep Saefullah; Nani Rohaeni; Tabroni Tabroni (International Journal of Engagement and Empowerment, 2022)
Partners in this Community Partnership Program (PKM) are the Kamurang Village Government and the managers of banana chips SMEs in Kamurang Village, Cikande District, Serang Regency. The objectives of this program are (1) to improve the knowledge and skills of partners in good and correct business management and business finance and understand business strategies in dealing with conditions in the new normal era, (2) to improve and develop digital marketing in marketing or sales of partner products and transfer of knowledge on the use of Appropriate Technology (TTG) in the form of making banana slicing machines, and (3) Assisting in the process of submitting a Certificate of Home Industry Food Production (SPP-IRT). By using the chronological method, the implementation of this activity resulted in an increase in partners' Knowledge and Skills regarding the management of Business Management, Business Finance, Digital Marketing and the application of Appropriate Technology (TTG) by 81.50%.